Psychosocial Pathways to Burnout in Women in High-Responsibility Caring Professions - Rahman, Farhana (Psychology of Woman Journal, 2026)
Objective: This study aimed to explore the psychosocial mechanisms contributing to burnout in women occupying high-responsibility caregiving roles, with an emphasis on emotional labor, institutional dynamics, and identity conflict. Methods and Materials: Using a qualitative exploratory design, semi-structured interviews were conducted with 22 women employed in leadership or supervisory positions within caregiving professions (e.g., healthcare, education, social work) across South Africa. Participants were selected using purposive sampling and interviews continued until theoretical saturation was achieved. Data were analyzed thematically using Braun and Clarke’s framework, supported by NVivo 14 software. Findings: Four major themes emerged from the analysis: (1) Emotional Labor and Compassion Fatigue, which encompassed empathic strain, emotional dissonance, and vicarious trauma; (2) Structural and Institutional Pressures, highlighting excessive workload, lack of resources, and gendered expectations in leadership; (3) Identity Conflict and Role Strain, which included work-life imbalance, internalized perfectionism, and identity fragmentation; and (4) Coping, Resilience, and Burnout Trajectories, where participants described both adaptive (e.g., mindfulness, peer support) and maladaptive (e.g., avoidance, emotional suppression) coping mechanisms. Emotional suppression, systemic neglect, and the invisibility of women’s labor emerged as key drivers in burnout progression. Conclusion: Burnout among women in high-responsibility caregiving roles is deeply rooted in psychosocial and structural contexts rather than individual weakness. Addressing this issue requires organizational reform, recognition of emotional labor, and the development of supportive policies that are gender-responsive and trauma-informed. This study contributes to a more nuanced understanding of the lived experiences of female professionals and underscores the urgent need for institutional interventions.